2019
DOI: 10.12659/msm.916661
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA (lncRNA) Small Nucleolar RNA Host Gene 5 (SNHG5) Regulates Proliferation, Differentiation, and Apoptosis of K562 Cells in Chronic Myeliod Leukemia

Abstract: BackgroundHuman chronic myelogenous leukemia (CML) is a hematopoietic stem cell disorder with high malignant and invasive activity. lncRNA SNHG5 has been reported to be upregulated in CML. However, whether it affects the proliferation, differentiation, and apoptosis in CML cells is still unknown. This study investigated the role of SNHG5 in CML and revealed the potential mechanism.Material/MethodsK562 cells were transfected with shRNA, and the expression level of SNHG5 was assessd by quantitative RT-PCR. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…14 Interestingly, DR4, an oncogene in the occurrence and development of tumors, was also involved in functional process of SNHG5. 22 In conclusion, these composite findings confirmed the imbalance of SNHG5 in AML and CML, forecasting its potential application in chemosensitivity.…”
Section: Endometrial Cancer (Ec)supporting
confidence: 58%
See 3 more Smart Citations
“…14 Interestingly, DR4, an oncogene in the occurrence and development of tumors, was also involved in functional process of SNHG5. 22 In conclusion, these composite findings confirmed the imbalance of SNHG5 in AML and CML, forecasting its potential application in chemosensitivity.…”
Section: Endometrial Cancer (Ec)supporting
confidence: 58%
“…21 Ma et al reported that the effect of SNHG5 on bladder cancer cells was partially involved with targeting p27. 23 Moreover, the methylation and downregulation of DR4 could also be induced by SNHG5 22 (Figure 3).…”
Section: Other Biological Moleculesmentioning
confidence: 96%
See 2 more Smart Citations
“…B Gao et al reported that inhibition of SNHG5 significantly inhibits K562 cell proliferation and induces cell differentiation by increasing the expression of CD42b, CD11b, CD14, GATA‐1, and β‐globin, also increases the expression of DR4 gene by inhibiting its methylation. They also found that by decreasing the expression of Bcl‐2 and increasing the expression of Bax and cleaved caspase‐3, SNHG5 significantly promotes cell apoptosis 50 …”
Section: Lncrna In Myeloid Malignanciesmentioning
confidence: 95%